The creation of Australia’s first "University of Specialisation" - McMullen, Gabrielle Lucy (Pacifica, 2015)
In the Australian context, the Melbourne College of Divinity (MCD) - since 2012 the University of Divinity - is a unique and successful ecumenical endeavour.1 With over 100 years as a leading provider of theological education and of service to its member churches, the MCD has also made history in progressing to become Australia’s first specialized university. This article traces the MCD’s historic transition to specialized university status.